Analisis Pembayaran Hutang dan Bunga oleh Debitur Pelaku Wanprestasi Berdasarkan Hukum Perdata - Moody Rizqy Syailendra; Angelica Ulinta Ginting; Irene Mariboto Sitanggang (Pusat Riset dan Inovasi Nasional, 2025)
A valid agreement creates a contract that gives rise to rights and obligations between the parties, and if one party does not fulfill its obligations, it can be declared to be in default. Default can be interpreted as the failure to fulfill or negligent in carrying out obligations as stipulated in the agreement made by the creditor and debtor. One example of a case of default regarding debts involving the Deputy Regent of Sidoarjo, Subandi, who borrowed IDR 1 billion from Darmiati Tansilong. The Supreme Court rejected Subandi's appeal (Decision No. 1609/K/Pdt/2022) and stated that he was in default. The Supreme Court's decision emphasized that the default committed by Subandi poses a risk in the form of debt repayment, paying profit sharing for property business development and the total interest that has been promised.